Novel Method for Rapid Detection of Spatiotemporal HIV Clusters Potentially Warranting Intervention - Arthur G. Fitzmaurice (Emerging Infectious Diseases, 2019)
Rapid detection of increases in HIV transmission enables targeted outbreak response efforts to reduce the number of new infections. We analyzed US HIV surveillance data and identified spatiotemporal clusters of diagnoses. This systematic method can help target timely investigations and preventive interventions for maximum public health benefit.